Extracellular Superoxide Dismutase Attenuates Hepatic Oxidative Stress in Nonalcoholic Fatty Liver Disease through the Adenosine Monophosphate-Activated Protein Kinase Activation - Heechul Nam; Ji Hee Lim; Tae Woo Kim; Eun Nim Kim; Sae-Jong Oum; Si Hyun Bae; Cheol Whee Park (MDPI AG, 2023)
Oxidative stress is key in type 2 diabetes-associated nonalcoholic fatty liver disease (NAFLD). We explored whether extracellular superoxide dismutase (EC-SOD) activates adenosine monophosphate-activated protein kinase (AMPK) to enhance antioxidant synthesis and lipid metabolism in NAFLD. Human recombinant EC-SOD (hEC-SOD) was administered to 8-week-old male C57BLKS/J db/db mice through intraperitoneal injection once a week for 8 weeks. Target molecules involved in oxidative stress and lipid metabolism were investigated. hEC-SOD improved insulin resistance and systemic and hepatic oxidative stress characterized by increases in urinary 8-hydroxy-deoxyguanosine and 8-isoprostane levels in db/db mice and a decrease in DHE expression in the liver, respectively. Hepatic SOD3 expression in db/db mice was reversed by hEC-SOD, which improved hepatic steatosis, inflammation with M2 polarization, apoptosis, autophagy, fibrosis and lipid metabolism in db/db mice, as reflected by the changes in serum and hepatic markers, monocyte chemoattractant protein-1, tumor necrosis factor-α, TUNEL-positive cells, Bcl-2/BAX ratio, beclin1 and LC3-II/LC3-1. At the molecular level, hEC-SOD increased phosphorylated-AMPK related to CaMKKß, activation of peroxisome proliferative-activated receptor-gamma coactivator (PGC)-1α and dephosphorylation of forkhead box O (FoxO)1 and their subsequent downstream signaling. In HepG2Cs cells using AMPKα1 and AMPKα2 siRNA, hEC-SOD demonstrated a protective effect via the direct activation of both AMPK-PGC-1α and AMPK-FoxO1. EC-SOD might be a potential therapeutic agent for NAFLD through the activation of AMPK-PGC-1α and AMPK-FoxO1 signaling in hepatocytes, which modulates lipid metabolism, leading to anti-inflammatory, antioxidative and antiapoptotic effects and improving autophagy in the liver.